2013
DOI: 10.1177/1534735413503546
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of a Home-Based Motivational Exercise Program for African American Breast Cancer Survivors

Abstract: Introduction. African American breast cancer survivors engage in less physical activity compared with their Caucasian counterparts. There is a need for exercise intervention research that focuses on improving the overall health and longterm survivorship of African American breast cancer survivors, especially because they often have worse outcomes than Caucasian survivors. Study objectives were to determine whether African American participants increase physical activity and explore whether exercise had a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 46 publications
2
70
0
Order By: Relevance
“…The current study is in agreement, showing positive trends in physical functioning after implementing exercise for eight weeks. Physical domains that found a positive trend in the current study included physical functioning, role limitations due to physical health, energy/fatigue, pain and general health that parallel other studies investigating the same domains [1,15,27]. In addition, mental domains contributing to a survivor's overall quality of life that showed a positive trend after the eight weeks included role limitations due to emotional health, emotional wellbeing and social functioning.…”
Section: Discussionsupporting
confidence: 80%
“…The current study is in agreement, showing positive trends in physical functioning after implementing exercise for eight weeks. Physical domains that found a positive trend in the current study included physical functioning, role limitations due to physical health, energy/fatigue, pain and general health that parallel other studies investigating the same domains [1,15,27]. In addition, mental domains contributing to a survivor's overall quality of life that showed a positive trend after the eight weeks included role limitations due to emotional health, emotional wellbeing and social functioning.…”
Section: Discussionsupporting
confidence: 80%
“…This review revealed that several studies included a group meeting or educational session. 11,14,1719,21,24,25,27,32,34,38–40,43–45 Across home-based 18,29,33,40,41 and telephone-based 36 studies, significant and nonsignificant results were reported. Another strategy identified, were phone calls from a peer counselor or research staff member.…”
Section: Resultsmentioning
confidence: 97%
“…The patient populations across the studies were heterogeneous, and included low-income women 30 , postpartum 31 , pregnant 32 , breast cancer survivors 33–35 , type 2 diabetes 19 , mobility disabilities 36 , and women with high-normal or untreated stage 1 hypertension. 22 Common inclusion criteria included overweight or obesity 15,18,26,32,34,36,37 and sedentary.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations